1993
DOI: 10.1093/geronj/48.5.p225
|View full text |Cite
|
Sign up to set email alerts
|

Axging, Inhibition, and Verbosity

Abstract: The hypothesis that off-target verbosity, defined as extended speech that is lacking in focus or coherence, is mediated by an age-related decline in the ability to inhibit task-irrelevant thoughts, was evaluated in a sample of 205 community-dwelling elderly volunteers aged 61-90. Results showed that performance on four tasks that measured the ability to suppress or remove irrelevant information stored in working memory accounted for a significant proportion of the variance in verbosity, whereas performance on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
216
4
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(250 citation statements)
references
References 0 publications
25
216
4
5
Order By: Relevance
“…For example, heightened response to irrelevant auditory and somatosensory stimuli (Knight & Grabowecky, 1995), diminished inhibition of reflexive but inappropriate saccades (Roberts, Hager, & Heron, 1994), and increased production of irrelevant, offgoal intrusion in speech (Arbuckle & Gold, 1993) are all 1 In addition, earlier studies may have failed to find belowbaseline suppression because those studies probably included a significant number of neutral-type younger adults, about whose performance little is known.…”
Section: Discussionmentioning
confidence: 99%
“…For example, heightened response to irrelevant auditory and somatosensory stimuli (Knight & Grabowecky, 1995), diminished inhibition of reflexive but inappropriate saccades (Roberts, Hager, & Heron, 1994), and increased production of irrelevant, offgoal intrusion in speech (Arbuckle & Gold, 1993) are all 1 In addition, earlier studies may have failed to find belowbaseline suppression because those studies probably included a significant number of neutral-type younger adults, about whose performance little is known.…”
Section: Discussionmentioning
confidence: 99%
“…However, this interpretation of age-related increases in verbose speech as due to feelings of isolation is contradicted by the findings of Gold, Andres, Arbuckle, and Schwartzman (1988). They explicitly tested for an association between increased verbosity and psychosocial behaviour and found that older socially outgoing adults were more verbose than older socially more isolated adults (see also Arbuckle & Gold, 1993;Pushkar, Basevitz, Arbuckle, Nohara-LeClair, Lapidus, & Peled, 2000).…”
Section: Ageing and Speech Production 243mentioning
confidence: 99%
“…Previous research has demonstrated that patients with frontal lobe dysfunction often show deficits in inhibition (e.g., perseveration and inability to maintain set; for reviews see Cronin-Golomb, 1990;Shimamura, 1995;Stuss & Benson, 1984), leading researchers to theorize that the frontal lobes are important for efficient inhibitory processing (Dempster, 1992;Kramer et al, 1994). It is commonly assumed in the neuropsychological literature that the WCST, verbal fluency test, and Trail Making Test reflect the functioning and integrity of the frontal lobes (e.g., Cronin-Golomb, 1990;Kramer et al, 1994;Lezak, 1995), and by extrapolation one can theorize that adequate performance on these tests may be partially dependent on intact inhibitory processes.Consistent with these arguments, Arbuckle and Gold (1993;Gold & Arbuckle, 1995) used these three neuropsychological measures as measures of inhibition in their study. The result of a factor analysis showed that these three neuropsychological measures (WCST, verbal fluency, and trails) fell out on one factor, which the authors hypothesized reflected inhibitory functioning.…”
mentioning
confidence: 95%
“…On the basis of an important study by Arbuckle and Gold (1993), our study used three neuropsychological tests to measure inhibitory functioning, namely the Wisconsin Card Sorting Test (WCST), the Trail Making Test, and a measure of verbal fluency. As also described by Arbuckle and Gold (1993), choice of these measures was based on arguments and evidence that each of the chosen tasks requires suppression of irrelevant or nongoal-directed information to make an appropriate response.The WCST (Milner, 1964) requires the participant to first sort cards according to one strategy, and then after a predetermined number of responses the sorting principle changes unbeknownst to the participant who then must alter his or her strategy and attempt to discover the new sorting Once the participant connects a number (or a letter), he or she must inhibit the preceding set to make the next response (to connect a letter or a number). The verbal fluency measure requires the individual to generate as many words as possible that begin with a presented letter within a time limit (Lezak, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation